CD46 TREM1 regulates the autophagy marker LC3B ATG5 in oral squamous cell carcinoma - Liu, Xiaodan; Zheng, Fumin; Gao, Meihua; Wang, Yuanfei; Lv, Xiaofang; Cong, Beibei; Wang, Wanchun (Frontiers in Oncology, 2025)
ObjectiveThis study aims to explore the regulatory effect of abnormal expression of CD46 and TREM1 on LC3B and ATG5 and to provide new targets for the molecular mechanism and treatment of OSCC. MethodsHuman oral squamous cell carcinoma cells CAL-27 were selected for in vitro culture. For related research, the CD46 shRNA interference test, immunohistochemistry (IHC), flow cytometry, qRT-PCR detection, Western blot, and tumor-bearing animal models were used. ResultsIn vitro cell experiments showed that CD46 and TREM1 were highly expressed on the surface of OSCC cells, while the expression of LC3B and ATG5 was significantly decreased. Compared with the control group (SC-shRNA), the CD46 shRNA group could effectively reduce the expression of CD46 in OSCC cells and increase the expression of autophagy and apoptosis protein (P<0.01). In vivo experiments showed that the tumor volume of the shRNA group was significantly smaller than that of the SC-shRNA group (P<0.01), the expression of CD46 and TREM1 was decreased considerably, and the expression of LC3B and ATG5 was higher (P<0.01). ConclusionOSCC cells have high expression of CD46 and TREM1, while low expression of LC3B and ATG5, and the autophagy apoptosis signal is weakened. Interfering with CD46 can up-regulate the expression of autophagy apoptosis genes, reduce the tumor inflammatory microenvironment, induce the apoptosis of OSCC cells, and inhibit the proliferation and metastasis of OSCC. This study provides a new idea for the mechanism and targeted therapy of OSCC and has important theoretical significance and clinical application value.